Efforts to Combat the Crime of Selling Abortion Products Through Social Media - Sishi Maudysari (Faculty of Law, Universitas Lampung, 2022)
Some people are currently misusing rapid technological advance to sell abortion drugs. This mode of selling abortion drugs is a type of crime that is difficult to prosecute because of the limitations of the rules in the Criminal Code. The problems in writing this paper are first, how are the police efforts in tackling the crime of selling abortion drugs through social media, second what are the inhibiting factors for the police in overcoming the sale of abortion products through social media. The method used in this research is using a normative juridical approach and an empirical juridical approach. Types of data consist of primary data and secondary data. The results of research and discussion were obtained by the police's efforts in dealing with criminal acts. The sale of abortion drugs through social media is the first through penal and non-penal efforts. The inhibiting factors for police efforts in overcoming the crime of selling abortion drugs through online media are, first, the lack of infrastructure facilities owned by the police IT; secondly, the human resources of the police in using the available facilities are not fully optimited also, there is no legal awareness of the community regarding the indifferent attitude of the community. It self last but not the problem of selling abortion drugs through social media should also be taken into account.